2016
DOI: 10.1073/pnas.1613722113
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanofiber coating with tunable combinatorial antibiotic delivery prevents biofilm-associated infection in vivo

Abstract: Bacterial biofilm formation is a major complication of implantable medical devices that results in therapeutically challenging chronic infections, especially in cases involving antibiotic-resistant bacteria.As an approach to prevent these infections, an electrospun composite coating comprised of poly(lactic-coglycolic acid) (PLGA) nanofibers embedded in a poly(e-caprolactone) (PCL) film was developed to locally codeliver combinatorial antibiotics from the implant surface. The release of each antibiotic could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 53 publications
0
76
0
Order By: Relevance
“…Recent in vivo studies demonstrated the feasibility and efficacy of tunable multi-layer nanocoatings that released different combinations of antibiotics 129 or sequential delivery of gentamicin and an osteoinductive growth factor 130 in a time-staggered manner for prevention of biofilm-associated infection and bone tissue repair around implants. Both studies demonstrated the ability to prevent biofilm formation on the device surface, relative to uncoated controls, with the nanocoatings able to clear infiltrating bacteria and prevented colonization of the implant while promoting bone formation and osseointegration.…”
Section: The Promise Of New Technologiesmentioning
confidence: 99%
“…Recent in vivo studies demonstrated the feasibility and efficacy of tunable multi-layer nanocoatings that released different combinations of antibiotics 129 or sequential delivery of gentamicin and an osteoinductive growth factor 130 in a time-staggered manner for prevention of biofilm-associated infection and bone tissue repair around implants. Both studies demonstrated the ability to prevent biofilm formation on the device surface, relative to uncoated controls, with the nanocoatings able to clear infiltrating bacteria and prevented colonization of the implant while promoting bone formation and osseointegration.…”
Section: The Promise Of New Technologiesmentioning
confidence: 99%
“…We found that the coatings with combinatorial release of vancomycin, daptomycin, or linezolid in conjunction with rifampin prevented a S. aureus (Xen36) infection in our K‐wire mouse model of OIAI . Moreover, using a near‐infrared fluorescent dye as a surrogate for antibiotic release from the coating, in vivo FLI imaging was employed to quantify and determine the duration of release of the fluorescent dye from the coating . Of note, the coating with combinatorial linezolid and rifampin release also prevented an MRSA (SAP231) infection in our rabbit model of OIAI .…”
Section: Treatmentmentioning
confidence: 80%
“…We found that the minocycline and rifampin‐releasing implant coating prevented the development of a S. aureus (strain ALC2906) infection in our K‐wire mouse model of OIAI . In addition, we used in vivo BLI imaging to evaluate the efficacy of a novel implant coating composed of poly(lactic‐co‐glycolic acid) and poly(ε‐caprolactone) nanofibers impregnated with single or combinatorial antibiotics . We found that the coatings with combinatorial release of vancomycin, daptomycin, or linezolid in conjunction with rifampin prevented a S. aureus (Xen36) infection in our K‐wire mouse model of OIAI .…”
Section: Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…63 Polymeric nanofibers, composed of PLGA and PCL, were developed by Ashbaugher et al for local co-delivery of a combination of antibiotics. 80 The release can be adjusted by varying the PLGA/PCL polymer ratio and proved to be highly effective in preventing medical device infections in patients. Benoit and co-workers synthesized positively charged nanoparticles from diblock copolymers composed of 2-(dimethylamino)ethyl methacrylate (DMAEMA), butyl methacrylate (BMA) and 2-propylacrylic acid (PAA) for loading with farnesil, a hydrophobic antibacterial drug.…”
Section: Polymer Nanoparticles and Hydrogelsmentioning
confidence: 99%